(untitled) (Research, Society and Development, 2022)
The education of ethnic-racial relations and intercultural dialogue represent a present and assured discussion in educational policies. Considering this, the objective of this research is to analyze the education of ethnic-racial relations and intercultural dialogue in the formation of teachers, pointing their spaces in the Common National Curricular Base (BNCC), as well as in the Common National Base for the Initial Training of Basic Education Teachers (BNC-Formation) for the formation of teachers of Basic Education. Methodologically, this study presents a qualitative approach, characterized as documentary, as we analyze documents such as BNCC and BNC for the formation of teachers of Basic Education in its preliminary version in the light of the content analysis of Bardin (2011). The results are characterized by the incipient introduction of this theme in these teacher education documents. In terms of conclusion, we realize the need to maintain these discussions in teacher education so that these documents that guide the educational policy of teacher education are not distant from other legislations.